Simultaneous carotid endarterectomy and myocardial revascularization by using cardiopulmonary bypass for both procedures - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2005)
Objective - The optimal treatment of patients with co-existing occlusive coronary and carotid arterial disease is controversial. This study reports our experience with simultaneous carotid endarterectomy and coronary bypass in conjunction with cardiopulmonary bypass with mild hypothermia. Methods and results - From March 2001 to June 2004, 72 patients underwent simultaneous coronary bypass and carotid endarterectomy. Their mean age was 68.9 years and there were 56 men and 16 women. The indication for carotid endarterectomy was a lumen diameter reduction of more than 75% and/or the presence of ulcerated/unstable plaque. Carotid endarterectomy was done during cardiopulmonary bypass under mild hypothermia, haemodilution, systemic heparinization and controlled haemodynamics under pulsatile perfusion for additional cerebral protection. The mean cardiopulmonary bypass time was 64.7 minutes and aortic cross-clamp time 32.4 minutes, and the mean number of grafts per patient was 2.7. Four patients had perioperative neurological complications (5.5%) and two had permanent deficits (2.7%). The procedure-related mortality was 3 (4.1%). Conclusions - We suggest that combining coronary revascularization and carotid endarterectomy and performing both under cardiopulmonary bypass is safe, offering acceptable morbidity and mortality rates.
Keywords: cardiopulmonary bypass; carotid endarterectomy; coronary artery bypass; simultaneous; CORONARY-ARTERY SURGERY; RISK-FACTORS; STROKE; DISEASE; PUMP; ASSOCIATION; OUTCOMES; STENOSIS